Luminal mucus plugs are spatially associated with airway wall thickening in severe COPD and asthma: A single-centered, retrospective, observational study. (October 2022) - Tran, Cecilia; Singh, Gaurav Veer; Haider, Ehsan; Boylan, Colm; Venegas, Carmen; Riaz, Shaista; Al Duwaiki, Suad; Yehia, Moustafa; Ho, Terence; Nair, Parameswaran; Svenningsen, Sarah; Kirby, Miranda
Abstract: Background: Airway wall thickening and excess airway mucus occur in asthma and chronic obstructive pulmonary disease (COPD), but few studies have investigated the relationship between them. Our objective was to determine the association between computed tomography (CT) airway wall thickening in segmental airways proximal to airways with or without mucus plugging in patients with asthma and COPD. Methods: Mucus plugging was scored using a CT bronchopulmonary segment-based scoring system in asthma and COPD patients. For each of the 19 segmental airways, a mucus plug was defined as complete occlusion of one or more of the daughter branches (sub-segmental airways) by mucus. CT airway measurements were generated for each of the 19 segmental airways: wall-area-percentage (WA%), lumen area (LA), and total airway count (TAC) (VIDA Diagnostics Inc.). Multivariable logistic regression models were constructed for the presence of mucus plugs with corresponding CT measurement and adjusted by covariates; each of the 19 segments was treated as a nested variable. Results: A total of 33 participants were evaluated. Participants had a mean age of 60 ± 15yrs and there were n = 14 (42%) males. There were 16 (48%) participants with a diagnosis of asthma and 17 (52%) with a COPD diagnosis. The mean FEV1 was 53 ± 21%pred and FEV1 /FVC was 54 ± 15%. The mean mucus score in all participants was 15 ± 4 (min = 0, max = 19). Multivariable logistic regression analysis showed the presence of airway mucus was significantly associated with increased CT WA% (β = 7.30, p = 0.004) and reduced TAC (β = −0.06, p = 0.045). Conclusions: There was increased airway wall thickness and reduced airway counts on CT in segments where there was a distal mucus plug compared to segments without mucus plugs in asthma and COPD. Highlights: In severe COPD and asthma patients, sub-segmental mucus prevalence was high. CT airway walls were thicker in airways with a distal mucus plug than without. Reduced airway counts on CT were associated with mucus plugs in the same segment.